Dysregulated RNA polyadenylation contributes to metabolic impairment in non-alcoholic fatty liver disease. Issue 6 (16th March 2022) - Jobbins, Andrew M; Haberman, Nejc; Artigas, Natalia; Amourda, Christopher; Paterson, Helen A B; Yu, Sijia; Blackford, Samuel J I; Montoya, Alex; Dore, Marian; Wang, Yi-Fang; Sardini, Alessandro; Cebola, Inês; et al.
Abstract: Pre-mRNA processing is an essential mechanism for the generation of mature mRNA and the regulation of gene expression in eukaryotic cells. While defects in pre-mRNA processing have been implicated in a number of diseases their involvement in metabolic pathologies is still unclear. Here, we show that both alternative splicing and alternative polyadenylation, two major steps in pre-mRNA processing, are significantly altered in non-alcoholic fatty liver disease (NAFLD). Moreover, we find that Serine and Arginine Rich Splicing Factor 10 ( SRSF10 ) binding is enriched adjacent to consensus polyadenylation motifs and its expression is significantly decreased in NAFLD, suggesting a role mediating pre-mRNA dysregulation in this condition. Consistently, inactivation of SRSF10 in mouse and human hepatocytes in vitro, and in mouse liver in vivo, was found to dysregulate polyadenylation of key metabolic genes such as peroxisome proliferator-activated receptor alpha ( PPARA) and exacerbate diet-induced metabolic dysfunction. Collectively our work implicates dysregulated pre-mRNA polyadenylation in obesity-induced liver disease and uncovers a novel role for SRSF10 in this process.